Leucodepletion for hyperleucocytosis – first report on a novel technology featuring electronic interphase management. Issue 1 (6th February 2013) - Schulz, M.; Bug, G.; Bialleck, H.; Serve, H.; Seifried, E.; Bönig, H.
<x xml:space="preserve">Abstract</x> Background and Objectives Therapeutic leucodepletion plays an established role in the initial treatment of patients with acute myeloid leukaemia (AML) and possibly other leukaemias presenting with leucostasis. Recently, a new leucodepletion technology, Spectra Optia IDL, has become available that differs from its predecessor, COBE Spectra MNC, by a variety of electronic supports, including by electronic adjustment of buffy coat positioning at the collection port. Given the paucity of patients in need of leucodepletions and marked differences in clinical presentation as well as blast properties (e.g. size, density), formal clinical trials comparing leucodepletion technologies have never been executed. Materials and Methods Here, we present aggregate data from eight leucodepletions performed in AML patients with clinical signs of leucostasis between 11/2011 and 07/2012 with the new device and compare the apheresis outcomes with those from fifteen leucodepletions performed with the old technology between 06/2010 and 10/2011. Results Patients did not differ with respect to epidemiological data. Pre‐apheresis leucocyte count (WBC) was significantly higher in Spectra Optia IDL patients. Tolerability was excellent with both devices. Basic apheresis denominators such as duration, processed volume, inlet pump rate, ACD‐A consumption and product volume were very similar. A negative correlation between pre‐apheresis WBC and collection efficiency was noted. Mean collection efficiency for leucocytes with Spectra Optia IDL (47·3%) was similar to that with COBE Spectra MNC (50·5%). Platelet attrition was similar with both devices, approximately 30%. Conclusion The novel, electronically guided leukapheresis system is suitable for leucodepletion.